2017
DOI: 10.1007/s12672-017-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

BRAF-Oncogene-Induced Senescence and the Role of Thyroid-Stimulating Hormone Signaling in the Progression of Papillary Thyroid Carcinoma

Abstract: Oncogene-induced senescence (OIS) explains the phenomenon of cellular senescence triggered by the action of oncogenes. It is a mechanism adopted by a cell to inhibit progression of benign tumors into malignancy, occurs in premalignant lesions, and is almost never present in malignant lesions. BRAF mutations occur in about 40-45% of all papillary thyroid carcinomas (PTCs) and of which 99.7% is the BRAFV600E mutation. A unique phenotype of the BRAFV600E mutation is the upregulation of the thyroid-stimulating hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…They generated a mouse colonderived organoid model with a Braf V600E mutant proto-oncogene that could be experimentally activated. Braf is a MAPK signalling gene whose upregulatory mutation can lead to either cell proliferation or, in pre-malignant lesions, to tumoursuppressing cell senescence (oncogene-induced senescence) [165]. Tao et al found that colon organoids expressing Braf V600E display a dysplastic phenotype when cultured for 2-3 months after Braf V600E activation.…”
Section: Stochastic and Age-related Factors Favouring Dna Hypermethylation And Diseasementioning
confidence: 99%
“…They generated a mouse colonderived organoid model with a Braf V600E mutant proto-oncogene that could be experimentally activated. Braf is a MAPK signalling gene whose upregulatory mutation can lead to either cell proliferation or, in pre-malignant lesions, to tumoursuppressing cell senescence (oncogene-induced senescence) [165]. Tao et al found that colon organoids expressing Braf V600E display a dysplastic phenotype when cultured for 2-3 months after Braf V600E activation.…”
Section: Stochastic and Age-related Factors Favouring Dna Hypermethylation And Diseasementioning
confidence: 99%
“…So far, we have only seen one case reported regarding BRAF mutation (c.1799 T>A;1801_1812del) in primary SCC of the thyroid (27). As we know that BRAF mutations, especially, BRAF V600E mutation is the most common molecular genetic change in PTC (28)(29)(30)(31)(32). Therefore, we believe that the SCC in the metastatic foci of this case may be evolved from the tall-cell subtype of PTC.…”
Section: Discussionmentioning
confidence: 75%
“…So far, we have only seen one case reported regarding BRAF mutation (c.1799 T > A; 1801_1812del) in primary SCC of the thyroid [27]. As we know that BRAF mutations, especially, BRAF V600E mutation is the most common molecular genetic change in PTC [28] [29] [30] [31] [32]. Therefore, we believe that the SCC in the metastatic foci of this case may be evolved from the tall-cell subtype of PTC.…”
Section: Discussionmentioning
confidence: 91%